(untitled) (Revista Brasileira de Contabilidade e Gestão, 2016)
This work proposes a process to evaluate the quality in use of an educational software, based on the SENAI Methodology of Professional Education, the Scratch tool, which is the object under study; the NBR ISO/IEC standards for evaluation of software quality; and the TUP (Technology, Usability, and Pedagogy) methodology of evaluation in the context of SENAI/SC. This work considered the following premise/hypothesis: is it possible to determine the influence of educational software in the teaching-learning process by respecting the quality criteria of software in use in a class of programming concepts or introduction to computer programming? A quali-quantitative research was used to evaluate this influence. The questionnaires were made available to a group of students of the industrial learning course in informatics at SENAI of Rio do Sul/SC during the programming concepts classes. The research was applied between March/2015 and April/2015. Preliminary results show that the Scratch software is an attractive tool and motivates the student to perform tasks during the teaching and learning process. Another point that stands out is that Scratch is a great tool to support teachers, thus showing that a well-applied educational tool creates a greater integration between theory and practice, a premise that is indicated and determined in the professional education methodology of SENAI/SC.